TSPO Modulates IL-4-Induced Microglia/Macrophage M2 Polarization via PPAR-γ Pathway - Zhou, Dandan; Ji, Lei; Chen, Youguo (Journal of molecular neuroscience, 2020)
Microglia activation has been reported to be associated with pathogenesis of neuroinflammation, central nervous system damage, and degeneration diseases. With various damage-associated molecules released, M1 polarization of microglia emerges early after injury and followed by M2 polarization. In this study, we demonstrate using a primary microglia polarization model that, during the M2 polarization of microglia, the protein expression of translocator protein (TSPO) was decreased and peroxisome proliferator–activated receptor (PPAR-γ) activation was observed. In addition, we found TSPO antagonist PK11195 treatment enhanced PPAR-γ expression in M2-polarized microglia, while TSPO agonist FGIN-1-27 and TSPO overexpression in microglia significantly suppressed PPAR-γ expression in both the cytoplasm and nucleus. Then, real-time quantitative PCR was used to detect the expression of M2 polarization markers in microglia after TSPO ligand treatment, the data showed that PK11195 promoted the expression of CD206, Arg-1, YM-1, and FIZZ-1 induced by interleukin-4 (IL-4), and FGIN-1-27 and TSPO overexpression inhibited the expression of these molecules. Furthermore, the release of BDNF, CNTF-1, IGF-1, and NGF-1 from microglia was determined by enzyme-linked immunosorbent assay; these trophic factors showed similar trends with expression of M2 polarization markers. Levels of BDNF, CNTF-1, IGF-1, and NGF-1 were obviously upregulated by PK11195 and downregulated by FGIN-1-27 and TSPO overexpression. We propose that IL-4 in the hypoxic ischemia brain site induces the M2 polarization of microglia, and TSPO inhibits the M2 polarization and trophic factor release through PPAR-γ pathway.